2017
DOI: 10.3390/nano7020045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon Nanotubes in Thermal Plasma Reactor at Atmospheric Pressure

Abstract: In this paper, a novel approach to the synthesis of the carbon nanotubes (CNTs) in reactors operating at atmospheric pressure is presented. Based on the literature and our own research results, the most effective methods of CNT synthesis are investigated. Then, careful selection of reagents for the synthesis process is shown. Thanks to the performed calculations, an optimum composition of gases and the temperature for successful CNT synthesis in the CVD (chemical vapor deposition) process can be chosen. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Szymanski et al [ 73 ] reported the synthesis of carbon nanotubes in a thermal plasma reactor at atmospheric pressure. The substrate for the synthesis was made of stainless steel and the substrate temperature (1000–1300 K) was controlled by the pyrometer.…”
Section: Synthesis Of Carbon Nanomaterialsmentioning
confidence: 99%
“…Szymanski et al [ 73 ] reported the synthesis of carbon nanotubes in a thermal plasma reactor at atmospheric pressure. The substrate for the synthesis was made of stainless steel and the substrate temperature (1000–1300 K) was controlled by the pyrometer.…”
Section: Synthesis Of Carbon Nanomaterialsmentioning
confidence: 99%
“…Carbon nanomaterials (CNMs) such as carbon nanotubes (CNTs), carbon nanofibers (CNFs) and carbon spheres (CSs) are materials which have remarkable physical and chemical properties, that include their strength and electrical conductivity [ 9 ], but their production processes are energy and resource intensive [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In recent years, researchers have suggested using plastic waste as a carbonaceous feedstock to make CNTs, CNFs and CSs [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs were synthesized by catalytic-chemical vapor deposition (CCVD) [4,9,10]. The apparatus used in the synthesis process was a three-zone horizontal furnace, allowing temperature control of each zone.…”
Section: Cnts Preparationsmentioning
confidence: 99%